52=(n+6)-4(-4+4n)

Simple and best practice solution for 52=(n+6)-4(-4+4n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52=(n+6)-4(-4+4n) equation:



52=(n+6)-4(-4+4n)
We move all terms to the left:
52-((n+6)-4(-4+4n))=0
We add all the numbers together, and all the variables
-((n+6)-4(4n-4))+52=0
We calculate terms in parentheses: -((n+6)-4(4n-4)), so:
(n+6)-4(4n-4)
We multiply parentheses
(n+6)-16n+16
We get rid of parentheses
n-16n+6+16
We add all the numbers together, and all the variables
-15n+22
Back to the equation:
-(-15n+22)
We get rid of parentheses
15n-22+52=0
We add all the numbers together, and all the variables
15n+30=0
We move all terms containing n to the left, all other terms to the right
15n=-30
n=-30/15
n=-2

See similar equations:

| (5-u)(4u-9)=0 | | 64-12y/40=37 | | 4z+8=2z+12 | | (x+3)=x-15 | | -8-5(-5a-7)=-98 | | 2z-6=3z+1 | | -4=w-10/5 | | 48=21d-7 | | 12+n=19n= | | 6(2x-8)=7x+17 | | 2(4x+5)=-43+37 | | 8x-14+3x=19 | | -3=9+7x | | 27-2700x^-2=0 | | 2x—x+4=13 | | 4z+1=19 | | 3(x+5)=4(2x+7)+2 | | 5x-4x2=9 | | 4x-5=-9;1 | | -4(3y+10)=-4 | | 8(6x-9)=4(7x-12) | | 8(6x-9)=48(7x-12) | | h/6+-1=-3 | | 2x-6+8x=10x-3+x | | 1(2y+-2)=-6 | | 9(2x-3)=8(3x-7) | | .7+9d=7d+3 | | -90=-15(k+5)-8k | | 3/8x-1/5=1/4 | | 6(5x-7)=7(3x8) | | 15b^2+9b=0 | | 80=10(t-2) |

Equations solver categories